Water and Nitrogen BMPs for Tomato and Watermelon: Water Quality and Economics - Sanjay Shukla; Gregory S. Hendricks; Fritz M. Roka; Thomas A. Obreza (EDIS, 2014)
Results of a two-year, four-crop-cycles experiment indicated that the recommended Best Management Practice (BMP) water and fertilizer nitrogen (N) rates for seepage-irrigated tomato in south Florida can reduce water use and N leaching to groundwater without adversely impacting yield. The same is true for watermelon for average rainfall conditions. This 5-page fact sheet was written by Sanjay Shukla, Gregory S. Hendricks, Fritz M. Roka, and Thomas A. Obreza, and published by the UF Department of Agricultural and Biological Engineering, May 2014.